Deregulated expression of VHL mRNA variants in papillary thyroid cancer. (5th March 2017) - Baldini, Enke; Tuccilli, Chiara; Arlot-Bonnemains, Yannick; Chesnel, Frank; Sorrenti, Salvatore; De Vito, Corrado; Catania, Antonio; D'Armiento, Eleonora; Antonelli, Alessandro; Fallahi, Poupak; Watutantrige-Fernando, Sara; Tartaglia, Francesco; et al.
Abstract: Recent findings demonstrated that a subset of papillary thyroid cancers (PTCs) is characterized by reduced expression of the von Hippel-Lindau ( VHL ) tumor suppressor gene, and that lowest levels associated with more aggressive PTCs. In the present study, the levels of the two VHL mRNA splicing variants, VHL-213 (V1) and VHL-172 (V2), were measured in a series of 96 PTC and corresponding normal matched tissues by means of quantitative RT-PCR. Variations in the mRNA levels were correlated with patients' clinicopathological parameters and disease-free interval (DFI). The analysis of VHL mRNA in tumor tissues, compared to normal matched tissues, revealed that its expression was either up- or down-regulated in the majority of PTC. In particular, V1 and V2 mRNA levels were altered, respectively, in 78 (81.3%) and 65 (67.7%) out of the 96 PTCs analyzed. A significant positive correlation between the two mRNA variants was observed (p < 0.001). Univariate analysis documented the lack of association between each variant and clinicopathological parameters such as age, tumor size, histology, TNM stage, lymph node metastases, and BRAF mutational status. However, a strong correlation was found between altered V1 or V2 mRNA levels and DFI. Multivariate regression analysis indicated higher V1 mRNA values, along with lymph node metastases at diagnosis, as independent prognostic factors predicting DFI. In conclusion, the data reported demonstrate that VHL gene expression is deregulated in the majority of PTC tissues. Of particular interest is the apparent protective role exerted by VHL transcripts against PTC recurrences. Highlights: Reduced expression of the VHL gene has been associated with more aggressive PTCs. Here we characterized the expression of the two VHL mRNA variants in PTC tissues. We showed that VHL gene expression is deregulated in the majority of PTC tissues. Of note is the protective role exerted by VHL transcripts against PTC recurrences.